Pengaruh Perubahan Organisasi dan Kompetensi Terhadap Kinerja Pegawai dengan Komitmen Organisasi Sebagai Mediasi: Studi pada ASN Kantor Imigrasi Kelas I TPI Semarang - Rihasto Mega Saputro; Euis Soliha (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Employee performance is the main capital for an organization to be able to maintain and develop its existence. Many things support human resources to have good quality and performance, one of which is organizational change, competence and organizational commitment. This study aims to analyze the effect of organizational change and competence on employee performance mediated by organizational commitment. The method used in sampling is a census sample, with a total of 95 respondents. The data analysis method used is multiple linear regression analysis. The test results show that there is a positive and significant influence between organizational change and competence on organizational commitment. There is a positive and significant influence between organizational change, competence and organizational commitment on employee performance. Organizational commitment is a good mediating variable, the influence of organizational change on employee performance and the influence of competence on employee performance